WHEN TRADITION AGAINST MODERNITY: Batak Angkola Men's Resistance towards Gender Equality - Nasution, Ulfa Ramadhani (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Modernity brings about gender equality, but in Padang Lawas, this gender equality is not universally accepted by Batak Angkola men. Resistance under the guise of masculine identity exists based on cultural reasons. This study aims to explore the reasoning behind Batak Angkola men's defense of their masculine identity in the public and domestic spheres amid the prevailing gender equality of the modern world. This study relies on a socio-anthropological approach. Data were obtained through observation and interviews. This study concludes that Batak Angkola men maintain their self-esteem (ego) and uphold their identity as part of the Batak patriarchy by using preventive cultural masculinity reasoning. This use of reasoning keeps them from being deprived of religious and cultural understanding. In essence, the modernity echoing gender equality auto-encourages Batak men to empower and safeguard their masculinity in their own ways and according to their own standards. This affirms that latently, Batak Angkola men's resistance to modernity is rooted in their traditional paradigm. Consequently, this is by no means enough to alleviate Batak women’s longstanding unfavorable circumstances, a double-burdened trap.[Modernitas melahirkan kesetaraan gender, namun di Padang Lawas kesetaraan gender ini tidak diterima secara universal oleh laki-laki Batak Angkola. Perlawanan dengan kedok identitas maskulin ada berdasarkan alasan budaya. Penelitian ini bertujuan untuk mengeksplorasi alasan di balik pembelaan identitas maskulin laki-laki Batak Angkola di ruang publik dan domestik di tengah kesetaraan gender yang berlaku di dunia modern. Kajian ini bersandar pada pendekatan sosio-antropologis. Data diperoleh melalui observasi dan wawancara. Penelitian ini menyimpulkan bahwa laki-laki Batak Angkola mempertahankan harga diri (ego) dan menjunjung tinggi identitasnya sebagai bagian dari patriarki Batak dengan menggunakan penalaran maskulinitas budaya preventif. Penggunaan penalaran ini membuat mereka tidak kehilangan pemahaman agama dan budaya. Intinya, modernitas yang menggemakan kesetaraan gender secara otomatis mendorong laki-laki Batak untuk memberdayakan dan menjaga kejantanannya dengan cara mereka sendiri dan menurut standar mereka sendiri. Hal ini menegaskan bahwa secara laten, resistensi laki-laki Batak Angkola terhadap modernitas berakar dari paradigma tradisional mereka. Konsekuensinya, ini sama sekali tidak cukup untuk meringankan keadaan tidak menguntungkan perempuan Batak yang sudah berlangsung lama, sebuah perangkap berbeban ganda.]